Interpretation and dating of the variant characters in the Houma Covenant. (June 2019) - Kang, Youn Ok
The Houma Covenant texts are complete and systematic oaths of alliance with clear writing and a neat structure. What is more striking is the amount of polymorphic characters contained in the Covenant. The most distinctive feature of the characters is their diversity, which is mainly reflected in the different writing styles and systems in various states. This paper probes the characteristics and laws of the internal structure of characters in the Spring and Autumn period and seeks to understand the characteristics of the polymorphic characters at that time. Through characters used in the Covenant, the paper aims to explore the dating signs of characters between the Spring and Autumn period and the Warring States. In this regard, the Houma Covenant undoubtedly provides us with hard-won data, giving us a definitive answer to the interpretation of the dating signs, and the phenomenon of polygraphs in the Houma Covenant can be roughly presented as a new and old form of the side of a Chinese character. In addition, the frequency of different forms of a character in variants for names is in accordance with the old and new order of glyphs. That is, the newer the glyph is, the more frequently it is used, and vice versa, which is also a notable trend in the glyphs of the Houma Covenant.